Vitrine de inovação IFB: fundamentos de design centrado no usuário aplicados a projeto de divulgação científica - Cary, Italo Rios (2021)
Communication strategies with structured innovation approaches focused on the human being can provide the Federal Institute of Brasilia (IFB) with means of recognizing, by society, the social role it represents through the results of research and innovative efforts carried out by professionals and students of the Institution. Thus, a study of audience profiles is presented as a way of contributing to the development, in time, of a digital platform that represents a showcase for the results of IFB's scientific production and that is conceived with user-oriented design principles. With a qualitative approach, the study is based on techniques such as bibliographic research and semi-structured interviews. To compose the study of users, 32 individual interviews were carried out, which took place mainly through videoconferencing applications, with video recording. The analysis of the content of the research data allowed the construction of four distinct user profiles, design personas, based on real characteristics observed in the investigated groups. It was concluded that the understanding of the needs, interests and behaviors of the different profiles that make up the social ecology of the IFB's scientific dissemination project, is fundamental for the establishment of more empathic and assertive forms of institutional communication.